2022
DOI: 10.1186/s12889-022-12827-4
|View full text |Cite
|
Sign up to set email alerts
|

The potential of food environment policies to reduce socioeconomic inequalities in diets and to improve healthy diets among lower socioeconomic groups: an umbrella review

Abstract: Socioeconomic inequalities in diets need to be tackled to improve population diets and prevent obesity and diet-related non-communicable diseases. The potential of food environment policies to reduce such inequalities has to date however not been appraised. The objective of this umbrella review was to assess the impact of food environment policies on socioeconomic inequalities in diets and to identify knowledge gaps in the existing literature, using the Healthy Food Environment Policy Index as a conceptual fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 63 publications
(121 reference statements)
1
20
0
Order By: Relevance
“…Differently than in other Food-EPI studies, in the PEN Food-EPI’s experts were also asked to prioritize the policy actions on equity. Experts in our study indicated that price actions have the greatest potential to reduce socioeconomic inequalities in diet, which was also shown by an umbrella and systematic review [ 63 , 64 ]. However, experts also indicated that food composition and marketing policies could be pro-equity, for which less empirical evidence was found [ 63 , 64 ].…”
Section: Discussionsupporting
confidence: 71%
“…Differently than in other Food-EPI studies, in the PEN Food-EPI’s experts were also asked to prioritize the policy actions on equity. Experts in our study indicated that price actions have the greatest potential to reduce socioeconomic inequalities in diet, which was also shown by an umbrella and systematic review [ 63 , 64 ]. However, experts also indicated that food composition and marketing policies could be pro-equity, for which less empirical evidence was found [ 63 , 64 ].…”
Section: Discussionsupporting
confidence: 71%
“…Policymakers could consider instituting an FE-linked policy for improving the community diet. The policy must address other FE-related issues such as nutritional composition, labelling, promotion, pricing, provision, retail, and investment [ 76 ]. In New Zealand, FE policy implementation led to excellent recommendations, such as the implementation of a national action plan for preventing non-communicable diseases, establishing priorities for reducing childhood and adolescent obesity, doubling funding for population nutrition promotion, and reducing the marketing of unhealthy foods [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The policy must address other FE-related issues such as nutritional composition, labelling, promotion, pricing, provision, retail, and investment [ 76 ]. In New Zealand, FE policy implementation led to excellent recommendations, such as the implementation of a national action plan for preventing non-communicable diseases, establishing priorities for reducing childhood and adolescent obesity, doubling funding for population nutrition promotion, and reducing the marketing of unhealthy foods [ 76 ]. In India, various nutrition interventions were formulated to enhance the FE through systematic planning and embracing differences in the problem for decoding and dividing to simplify resolutions to be addressed by policymakers and nutritionists in the future [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that some groups are more prone to develop overweight or obesity. Therefore, it is important implement policies that target this socio-demographic gradient in cases [62]. Without taking action, the rise in cases will likely follow the projected trajectory, whereby the rates of disease burden and associated healthcare cost of non-communicable diseases will also rise [63,64].…”
Section: Policy Implicationsmentioning
confidence: 99%